Intermolecular interactions of the malate synthase of Paracoccidioides spp - Oliveira, Karine Martins de; Silva Neto, Benedito Rodrigues da; Parente, Juliana Alves; Silva, Roosevelt Alves da; Quintino, Guilherme Oliveira; Voltan, Aline Raquel [UNESP]; Mendes-Giannini, Maria José Soares [UNESP]; Almeida Soares, Célia Maria de; Pereira, Maristela (Springer Nature, 2013)
Background: The fungus Paracoccidioides spp is the agent of paracoccidioidomycosis (PCM), a pulmonary mycosis acquired by the inhalation of fungal propagules. Paracoccidioides malate synthase (PbMLS) is important in the infectious process of Paracoccidioides spp because the transcript is up-regulated during the transition from mycelium to yeast and in yeast cells during phagocytosis by murine macrophages. In addition, PbMLS acts as an adhesin in Paracoccidioides spp. The evidence for the multifunctionality of PbMLS indicates that it could interact with other proteins from the fungus and host. The objective of this study was to identify and analyze proteins that possibly bind to PbMLS (PbMLS-interacting proteins) because protein interactions are intrinsic to cell processes, and it might be possible to infer the function of a protein through the identification of its ligands. Results: The search for interactions was performed using an in vivo assay with a two-hybrid library constructed in S. cerevisiae; the transcripts were sequenced and identified. In addition, an in vitro assay using pull-down GST methodology with different protein extracts (yeast, mycelium, yeast-secreted proteins and macrophage) was performed, and the resulting interactions were identified by mass spectrometry (MS). Some of the protein interactions were confirmed by Far-Western blotting using specific antibodies, and the interaction of PbMLS with macrophages was validated by indirect immunofluorescence and confocal microscopy. In silico analysis using molecular modeling, dynamics and docking identified the amino acids that were involved in the interactions between PbMLS and PbMLS-interacting proteins. Finally, the interactions were visualized graphically using Osprey software. Conclusion: These observations indicate that PbMLS interacts with proteins that are in different functional categories, such as cellular transport, protein biosynthesis, modification and degradation of proteins and signal transduction. These data suggest that PbMLS could play different roles in the fungal cell. © 2013 de Oliveira et al.; licensee BioMed Central Ltd.
Keywords: Malate synthase; Paracoccidioides spp; Protein-protein interactions; malate synthase; amino acid analysis; amino acid sequence; antibody production; antibody specificity; computer model; computer program; confocal microscopy; controlled study; Far Western blotting; genetic transcription; heterologous expression; immunofluorescence; in vivo study; ligand binding; lung alveolus cell; macrophage; mass spectrometry; molecular docking; molecular dynamics; molecular interaction; molecular model; mycelium; Paracoccidioides; protein analysis; protein binding; protein determination; protein function; protein interaction; protein protein interaction; protein purification; protein secretion; Saccharomyces cerevisiae; sequence homology; signal transduction; two hybrid system; yeast; Fungi; Murinae